2016
DOI: 10.1088/1674-1056/25/7/070301
|View full text |Cite
|
Sign up to set email alerts
|

Gazeau–Klauder coherent states examined from the viewpoint of diagonal ordering operation technique

Abstract: In this paper we investigate the Gazeau-Klauder coherent states using a newly introduced diagonal ordering operation technique, in order to examine some of the properties of these coherent states. The results coincide with those obtained from other purely algebraic methods, but the calculations are greatly simplified. We apply the general theory to two cases of Gazeau-Klauder coherent states: pseudoharmonic as well as the Morse oscillators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The DOOT can be applied also in order to construct the CSs in the Gazeau-Klauder manner [24]. Moreover, by the help of DOOT, we have showed that the coherent states for the continuous spectrum can be regarded as the limiting case of hypergeometric Barut-Girardello coherent states (GH-BG-CSs) [25].…”
Section: Some Applicationsmentioning
confidence: 99%
“…The DOOT can be applied also in order to construct the CSs in the Gazeau-Klauder manner [24]. Moreover, by the help of DOOT, we have showed that the coherent states for the continuous spectrum can be regarded as the limiting case of hypergeometric Barut-Girardello coherent states (GH-BG-CSs) [25].…”
Section: Some Applicationsmentioning
confidence: 99%
“…In a series of previous works, we have generalized the IWOP technique and applied it to the pair of creation 􏽢 E + , and annihilation 􏽢 E − , operators associated with any quantum system, linear or nonlinear. us, it was born the diagonal operator ordering technique (DOOT) was born, with which we obtained a series of useful results [17][18][19]. An additional result of using DOOT appears in this paper: we obtain a series of new integration relations involving Meijer's G m,n p,q (|z| 2 | .…”
Section: Introductionmentioning
confidence: 97%
“…In 1999, Gazeau and Klauder (GK) [18] proposed new coherent states for semibounded Hamiltonian operators having either a discrete or continuous spectrum. These states, which have been constructed for a large variety of quantum systems [19][20][21][22][23][24][25][26][27], also satisfy the Klauderʼs minimum requirements.…”
Section: Introductionmentioning
confidence: 97%